Physicochemical characterization and cytotoxicity of chitosan-modified single walled carbon nanotubes as drug carriers - Zhang, Xiao Xue; Huang, Hao Yan; Chen, Li Qing; Jin, Hehua; Lee, Beom Jin; Cui, Jing Hao; Cao, Qing Ri (Journal of Pharmaceutical Investigation, 2019)
The application of single-walled carbon nanotubes (SWCNTs) as drug carriers is limited by their poor dispersal in aqueous medium. This study aimed to prepare chitosan (CS)-modified SWCNTs (CS-SWCNTs) and to evaluate their physicochemical properties and cytotoxicity. Oxidized SWCNTs (O-SWCNTs) were prepared with the use of strong acid, and the effects of acidizing conditions on the oxidation degree of the O-SWCNTs were investigated. CS was then non-covalently modified on the surfaces of O-SWCNTs. O-SWCNTs and CS-SWCNTs were characterized through ultraviolet spectroscopy, Fourier transform-infrared spectroscopy, Raman spectroscopy, and transmission electron microscopy. The cytotoxic effects of the functionalized SWCNTs were determined through the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay. O-SWCNTs with relatively complete structure were successfully synthesized through 5 h of treatment with 5 M acid. The amine group of the CS and the carboxyl group of O-SWCNTs interacted in CS-SWCNTs. The functionalized SWCNTs did not aggregate or precipitate in water and exerted no cytotoxic effects on A549 and MCF-7 tumor cells. The CS-SWCNTs possess the advantages of a simple preparation process, excellent water dispersibility, and biocompatibility for drug loading.
Keywords: Carbon nanotubes; Chitosan; Cytotoxicity; Raman spectroscopy; TEM; X-ray diffraction